Steel foil for current collectors, electrodes, and batteries
Patent Information
- Application Number
- JP2023511343
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-03-31
- Filing Date
- 2022-03-29
- Publication Date
- 2025-02-17
- Estimated Expiration
- 2042-03-29
Smart Images

Figure 0007630605000003 
Figure 0007630605000004 
Figure 0007630605000001
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a steel foil for a current collector used in an electrode of a battery, an electrode using the steel foil for a current collector, and a battery using the electrode. [Background technology]
[0002] Up to now, batteries such as primary batteries and secondary batteries have been used as power sources for various electronic devices. Specifically, in recent years, secondary batteries, such as lithium ion batteries, have rapidly become popular due to the widespread use of small electronic devices such as home video cameras, laptops, and smartphones. As such small electronic devices become smaller and more powerful, batteries are required to be further miniaturized and have improved performance. In this specification, the term "secondary battery" refers to, for example, a non-aqueous electrolyte secondary battery, an aqueous electrolyte secondary battery, and an all-solid-state secondary battery.
[0003] The battery includes an electrode, a separator, and an electrolyte. The electrode includes a positive electrode and a negative electrode. In both the positive electrode and the negative electrode, an electrode mixture layer is formed on a current collector. The current collector is a base material of the electrode. The electrode mixture layer is a layer containing an active material and a binder. The current collector has a function of supplying a current to the active material and a function of holding the active material. Until now, metal foils have been used as current collectors. Specifically, for example, in lithium ion batteries, copper foil is currently used as the negative electrode current collector, and aluminum foil is currently used as the positive electrode current collector.
[0004] The active material means a material capable of absorbing and releasing ions of an electrolyte. Specifically, for example, in lithium ion batteries, graphite-based carbon materials are currently used as negative electrode active materials, and oxides such as LiCoO2 are currently used as positive electrode active materials. The binder has the function of binding active materials together and between active materials and current collectors. The binder is, for example, a resin.
[0005] The separator is placed between the positive and negative electrodes as an insulator to prevent electrical short circuits. For example, in lithium-ion batteries, a porous organic film is currently used as the separator. The electrolyte exchanges ions with the positive and negative electrodes. In recent years, not only liquid electrolytes but also solid electrolytes have been developed.
[0006] As described above, further miniaturization and performance improvement are required for batteries. Therefore, based on miniaturization and performance improvement, the current collector is required to have a strength higher than that of the above-mentioned copper foil and aluminum foil. Therefore, as a substrate for the current collector, attention has been paid to steel foil, which is an iron-based metal foil that is superior in strength and heat resistance to copper foil and aluminum foil.
[0007] JP 2012-33470 A (Patent Document 1) and WO 2013 / 157598 A (Patent Document 2) propose steel foils for current collectors.
[0008] The steel foil disclosed in Patent Document 1 has a core material (base material) made of steel, and both sides of the core material are coated with a film having an average thickness of t Cu The copper coating layer has an average thickness t of 0.02 to 5.0 μm. Cu / t is 0.3 or less. Patent Document 1 discloses that this steel foil can provide a negative electrode current collector with higher strength and durability.
[0009] The steel foil disclosed in Patent Document 2 has a chemical composition containing, in mass%, C: 0.0001-0.02%, Si: 0.001-0.01%, Mn: 0.01-0.3%, P: 0.001-0.02%, S: 0.0001-0.01%, Al: 0.0005-0.1%, and N: 0.0001-0.004%, with the balance being Fe and impurities. This steel foil further has a thickness of 5-15 μm and a tensile strength of more than 900 to 1200 MPa. This steel foil is lightweight and economical, and Patent Document 2 discloses that this steel foil can provide a steel foil for a negative electrode current collector that has both strength and electrical resistance. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] JP 2012-33470 A [Patent Document 2] International Publication No. 2013 / 157598 Summary of the Invention [Problem to be solved by the invention]
[0011] As proposed in the above Patent Documents 1 and 2, a lightweight and high-strength current collector can be obtained by using steel foil. However, when steel foil is used as a current collector, adhesion to the electrode mixture layer may decrease. When the adhesion of the current collector steel foil to the electrode mixture layer is low, the electrode mixture layer is likely to peel off from the current collector steel foil. As a result, an electrode comprising a current collector steel foil and an electrode mixture layer cannot fully exhibit its function. However, the above Patent Documents 1 and 2 do not consider the adhesion between the steel foil and the electrode mixture layer.
[0012] As described above, in an electrode, the steel foil for a current collector has a function of supplying a current to the active material of the electrode mixture layer. Here, if the electrical conductivity of the electrode is reduced, the electromotive force of the battery may be reduced. If the electrical conductivity of the electrode is reduced, the electrode may generate heat during use as a battery, and the battery life may be shortened. Therefore, it is preferable that the electrical conductivity of the electrode obtained by forming an electrode mixture layer on the surface of the steel foil for a current collector is high. However, the above Patent Documents 1 and 2 do not consider the electrical conductivity of the electrode obtained by forming an electrode mixture layer on the surface of the steel foil for a current collector.
[0013] An object of the present disclosure is to provide a steel foil for a current collector that has high adhesion to an electrode mixture layer and can enhance electrical conductivity when an electrode mixture layer is formed on the surface thereof, an electrode using the steel foil for a current collector, and a battery using the electrode. [Means for solving the problem]
[0014] The steel foil for a current collector according to the present disclosure is A substrate and a Ni plating layer formed on a surface of the substrate, When the arithmetic mean roughness of the surface of the Ni plating layer is defined as Ra, the average distance between peaks formed on the surface of the Ni plating layer and identified by line roughness analysis is defined as D, and the average radius of curvature of the peaks formed on the surface of the Ni plating layer and identified by area roughness analysis is defined as r, Ra×D is 0.060~0.400μm 2 and r is 0.010 to 0.500 μm.
[0015] The electrode according to the present disclosure comprises: The current collector steel foil, and an electrode mixture layer formed on the surface of the current collector steel foil.
[0016] The battery according to the present disclosure comprises: The electrode; A separator; and an electrolyte. Effect of the Invention
[0017] The steel foil for a current collector according to the present disclosure has high adhesion to an electrode mixture layer and has high electrical conductivity when an electrode mixture layer is formed on the surface. The electrode according to the present disclosure has high adhesion between the steel foil for a current collector and the electrode mixture layer and has high electrical conductivity. [Brief description of the drawings]
[0018] [Figure 1] FIG. 1 is a diagram showing the relationship between the value obtained by multiplying the arithmetic mean roughness Ra of the Ni plating layer surface of the current collector steel foil in this embodiment by the average distance D (μm2) between peaks formed on the Ni plating layer surface and identified by line roughness analysis, and the penetration resistance (relative value), which is an index of the electrical conductivity of the current collector steel foil on which an electrode mixture layer is formed. [Diagram 2]FIG. 2 is a diagram showing the relationship between the average radius of curvature r (μm) of the peaks formed on the surface of the Ni plating layer of the current collector steel foil in this embodiment and identified by surface roughness analysis, and the peel strength (N / m), which is an index of adhesion of the current collector steel foil to the electrode mixture layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] The present inventors have investigated means for improving the adhesion between a steel foil and an electrode mixture layer and for improving the electrical conductivity of the steel foil for a current collector on which an electrode mixture layer is formed, when the steel foil is used as a current collector. As a result, the following findings have been obtained.
[0020] Steel foils often have a smooth surface compared to other metal foils. In particular, steel foils manufactured by cold rolling have a very smooth surface. The present inventors thought that the high smoothness of the surface of steel foils makes it easier for the adhesion of steel foils to the electrode mixture layer to decrease compared to other metal foils. That is, by roughening the surface of the steel foil, it is possible to increase the adhesion of the steel foil to the electrode mixture layer. Therefore, the present inventors considered forming a coating on the surface of the steel foil (substrate) to produce a steel foil for a current collector having a rough surface.
[0021] The electrode mixture layer contains a binder, typically a resin. The binder usually has low electrical conductivity. Therefore, in the region of the interface between the collector steel foil and the electrode mixture layer where the binder is present, current does not flow easily. That is, contact resistance may occur at the interface between the collector steel foil and the electrode mixture layer. If the contact resistance at the interface between the collector steel foil and the electrode mixture layer increases, the electrical conductivity of the electrode obtained by forming the electrode mixture layer on the surface of the collector steel foil decreases.
[0022] That is, when a steel foil for a current collector having a rough surface is produced by forming a coating on the surface of a substrate, if the electrical conductivity of the coating is low, the electrical conductivity of an electrode produced from the steel foil for a current collector is reduced. Therefore, the present inventors have conducted detailed studies on a means for roughening the surface of the steel foil for a current collector without impairing the electrical conductivity of the electrode. As a result, the present inventors have found that it is possible to achieve both adhesion and electrical conductivity by forming a Ni plating layer having an uneven surface.
[0023] It is believed that if a plating layer having an uneven shape is formed on the surface of the substrate, the electrode mixture layer will penetrate into the uneven shape, and the electrode mixture layer will not easily peel off from the steel foil for the current collector. In other words, it is possible that the adhesion of the steel foil for the current collector to the electrode mixture layer can be improved. Furthermore, it is believed that the uneven shape increases the surface area where the steel foil for the current collector and the electrode mixture layer come into contact. As a result, the amount of active material in contact with the steel foil for the current collector increases, and it is possible to reduce the contact resistance occurring at the interface between the steel foil for the current collector and the electrode mixture layer. Furthermore, if a Ni plating layer is formed on the surface of the substrate, it is possible to suppress the formation of an oxide film on the surface of the substrate made of steel. In other words, it is possible to improve the electrical conductivity of the electrode made of the steel foil for the current collector.
[0024] Therefore, the present inventors manufactured various steel foils for current collectors in which a Ni plating layer having an uneven shape was formed on the surface of a substrate, and evaluated the adhesion of the steel foil for current collectors to an electrode mixture layer and the electrical conductivity of the steel foil for current collectors on which an electrode mixture layer was formed. As a result of detailed studies by the present inventors, it became clear that in order to achieve both adhesion and electrical conductivity, it is not enough to simply increase the roughness of the surface of the Ni plating layer, but it is effective to control the shape of the surface of the Ni plating layer. In other words, contrary to the expectations of the present inventors, it became clear that simply increasing the arithmetic mean roughness of the surface of the Ni plating layer does not allow the adhesion and electrical conductivity of the steel foil for current collectors on which an electrode mixture layer was formed to be compatible.
[0025] As a result of further detailed investigations by the present inventors, it has become clear that in order to achieve both adhesion and electrical conductivity of a steel foil for a current collector having an electrode mixture layer formed thereon, it is necessary to control the arithmetic mean roughness Ra of the surface of the Ni plating layer, the average distance D between the peaks formed on the surface of the Ni plating layer, and the average radius of curvature r of the peaks formed on the surface of the Ni plating layer.
[0026] Specifically, in the steel foil for a current collector according to the present embodiment, when the arithmetic mean roughness of the surface of the Ni plating layer is defined as Ra, the average distance between peaks formed on the surface of the Ni plating layer and identified by line roughness analysis is defined as D, and the average radius of curvature of the peaks formed on the surface of the Ni plating layer and identified by surface roughness analysis is defined as r, Ra×D is 0.060 to 0.400 (μm 2 ) and r is 0.010 to 0.500 (μm), the adhesion of the current collector steel foil to the electrode mixture layer and the electrical conductivity of the current collector steel foil on which the electrode mixture layer is formed are improved. This point will be described in detail with reference to the drawings.
[0027] FIG. 1 shows the Ra×D (μm 2 1 is a graph showing the relationship between Ra×D (μm) and the penetration resistance (relative value), which is an index of electrical conductivity. 2 ) and the penetration resistance (relative value), which is an index of electrical conductivity. The penetration resistance (relative value) was determined by the method described below. The lower the penetration resistance, the higher the electrical conductivity.
[0028] Referring to FIG. 1, in the steel foil on which the Ni plating layer was formed, Ra×D was 0.060 (μm 2 ) or more, it can be confirmed that the electrical conductivity of the steel foil for a current collector on which an electrode mixture layer is formed is increased. Therefore, in this embodiment, it is preferable to set Ra×D to 0.060 (μm 2 ) or more.
[0029] Fig. 2 is a diagram showing the relationship between r (μm) in this example and peel strength (N / m), which is an index of adhesion. Fig. 2 was created using r (μm) and peel strength (N / m), which is an index of adhesion, for an example in which a Ni plating layer is formed on the surface of a steel foil, among the examples described later. The peel strength (N / m) was determined by the method described later. A higher peel strength indicates a higher adhesion.
[0030] 2, it can be confirmed that in the steel foil having a Ni plating layer, when r is 0.500 (μm) or less, the adhesion of the steel foil for a current collector to the electrode mixture layer is improved compared to when r is more than 0.500 (μm). Therefore, in this embodiment, r is set to 0.500 (μm) or less.
[0031] Therefore, the steel foil for a current collector according to the present embodiment includes a substrate and a Ni plating layer formed on the surface of the substrate, and the surface of the Ni plating layer has a Ra×D of 0.060 to 0.400 (μm 2 ) and r is 0.010 to 0.500 (μm). As a result, the steel foil for a current collector according to this embodiment has high adhesion to the electrode mixture layer, and further, the steel foil for a current collector on which the electrode mixture layer is formed has high electrical conductivity.
[0032] The details of why controlling not only the arithmetic mean roughness Ra of the Ni plating layer surface but also the average distance D between peaks formed on the Ni plating layer surface and the average curvature radius r of the peaks formed on the Ni plating layer surface is effective for the adhesion and electrical conductivity of the steel foil for a current collector on which an electrode mixture layer is formed have not been clarified. However, the present inventors speculate as follows.
[0033] Here, the arithmetic mean roughness Ra of the surface of the Ni plating layer is an index showing the size of the uneven shape of the Ni plating layer surface. That is, the larger the arithmetic mean roughness Ra, the larger the unevenness formed on the Ni plating layer surface on average. In addition, the average distance D between the peaks formed on the surface of the Ni plating layer is an index showing the density of the unevenness in the uneven shape of the Ni plating layer surface. That is, the smaller the average distance D between the peaks, the denser the unevenness formed on the Ni plating layer surface.
[0034] When the arithmetic mean roughness Ra of the Ni plating layer surface is large and the average distance D between the peaks formed on the Ni plating layer surface is too small, large irregularities are formed densely on the Ni plating layer surface. In this case, the electrode mixture layer may not easily enter the irregularities formed on the Ni plating layer surface. As a result, a gap may be generated between the Ni plating layer and the electrode mixture layer, and the surface area of contact between the steel foil for current collector and the electrode mixture layer may become smaller. As a result, the present inventors speculate that even if the arithmetic mean roughness Ra of the Ni plating layer surface is large, the electrical conductivity of the steel foil for current collector on which the electrode mixture layer is formed may decrease.
[0035] In addition, when the arithmetic mean roughness Ra of the Ni plating layer surface is large and the average distance D between the peaks formed on the Ni plating layer surface is too large, large irregularities are formed sparsely on the Ni plating layer surface. In this case, the number of irregularities on the Ni plating layer surface is small, and the surface area of contact between the Ni plating layer and the electrode mixture layer may not be sufficiently large. As a result, the present inventors speculate that even if the arithmetic mean roughness Ra of the Ni plating layer surface is large, the electrical conductivity of the steel foil for current collector on which the electrode mixture layer is formed may decrease.
[0036] The average radius of curvature r of the peaks formed on the surface of the Ni plating layer is an index showing the sharpness of the uneven shape of the surface of the Ni plating layer. Even if the arithmetic mean roughness Ra of the surface of the Ni plating layer is large, if the average radius of curvature r of the peaks formed on the surface of the Ni plating layer is too large, there is a possibility that a sufficient anchor effect on the electrode mixture layer cannot be obtained. As a result, the present inventors speculate that even if the arithmetic mean roughness Ra of the surface of the Ni plating layer is large, sufficient adhesion to the electrode mixture layer cannot be obtained.
[0037] The present inventors speculate that, by controlling not only the arithmetic mean roughness Ra of the surface of the Ni plating layer but also the average distance D between the peaks formed on the surface of the Ni plating layer and the average radius of curvature r of the peaks formed on the surface of the Ni plating layer, the adhesion to the electrode mixture layer is improved, and furthermore, the electrical conductivity of the steel foil for a current collector on which the electrode mixture layer is formed is improved, by a mechanism different from the above-mentioned mechanism, by controlling not only the arithmetic mean roughness Ra of the surface of the Ni plating layer but also the average distance D between the peaks formed on the surface of the Ni plating layer and the average radius of curvature r of the peaks formed on the surface of the Ni plating layer, the adhesion to the electrode mixture layer is improved, and furthermore, the electrical conductivity of the steel foil for a current collector on which the electrode mixture layer is formed is improved. However, in the steel foil for a current collector according to this embodiment, the surface of the Ni plating layer has a Ra×D of 0.060 to 0.400 (μm 2 ) and r is 0.010 to 0.500 (μm), the adhesion to the electrode mixture layer is high, and further, the electrical conductivity of the steel foil for a current collector on which the electrode mixture layer is formed is high, as will be demonstrated by the examples described later.
[0038] The gist of the current collector steel foil, electrode, and battery according to the present embodiment, which have been completed based on the above findings, is as follows.
[0039] [1] A steel foil for a current collector, A substrate and a Ni plating layer formed on a surface of the substrate, When the arithmetic mean roughness of the surface of the Ni plating layer is defined as Ra, the average distance between peaks formed on the surface of the Ni plating layer and identified by line roughness analysis is defined as D, and the average radius of curvature of the peaks formed on the surface of the Ni plating layer and identified by area roughness analysis is defined as r, Ra×D is 0.060~0.400μm 2 and r is 0.010 to 0.500 μm; Steel foil for current collectors.
[0040] [2] The steel foil for a current collector according to [1], The average thickness of the substrate is 5 to 30 μm. Steel foil for current collectors.
[0041] [3] [1] or [2], and An electrode mixture layer formed on the surface of the current collector steel foil, electrode.
[0042] [4] [3] The electrode according to the present invention; A separator; an electrolyte; battery.
[0043] Hereinafter, the steel foil for a current collector according to this embodiment, the electrode according to this embodiment, and the battery according to this embodiment will be described.
[0044] [Steel foil for current collectors] The current collector steel foil according to the present embodiment includes a substrate and a Ni plating layer formed on the surface of the substrate. As described above, in this specification, "steel foil" means a steel plate having a thickness of 50 μm or less. In short, the thickness of the current collector steel foil according to the present embodiment is 50 μm or less. The thinner the current collector steel foil is, the higher the energy density of a battery using an electrode manufactured using the current collector steel foil is. However, if the current collector steel foil is too thin, it becomes difficult to manufacture the current collector steel foil.
[0045] [Base material] In this embodiment, the substrate is an iron-based metal foil (steel foil). That is, in the chemical composition of the substrate, the content is greatest in iron (Fe). The substrate may be a carbon steel foil or a stainless steel foil. When the substrate is a stainless steel foil, the type of stainless steel is not particularly limited, and may be, for example, a ferritic stainless steel foil, a martensitic stainless steel foil, an austenitic stainless steel foil, a ferritic-martensitic duplex stainless steel foil, or a ferritic-austenitic duplex stainless steel foil.
[0046] In this embodiment, the preferred upper limit of the thickness of the substrate is 45 μm, more preferably 40 μm, more preferably 35 μm, and more preferably 30 μm. In this embodiment, the preferred lower limit of the thickness of the substrate is 1 μm, more preferably 3 μm, and more preferably 5 μm. In short, in this embodiment, the thickness of the substrate is preferably 5 to 30 μm. In this case, the substrate can be stably manufactured, and the energy density is further increased in a battery using an electrode manufactured using the substrate.
[0047] [Ni plating layer] In the steel foil for current collector according to the present embodiment, a Ni plating layer is formed on the surface of the substrate. The chemical composition of the Ni plating layer is composed of Ni and impurities. The thickness of the Ni plating layer is not particularly limited. The thickness of the Ni plating layer is, for example, 1 to 20 μm. If the Ni plating layer is too thick, the steel foil for current collector becomes too thick, which runs counter to the industrial demand for miniaturization of secondary batteries. On the other hand, if the Ni plating layer is too thin, it becomes difficult to form a uniform Ni plating layer on the surface of the substrate. Therefore, in the present embodiment, the preferred thickness of the Ni plating layer is 1 to 20 μm. The thickness of the Ni plating layer according to the present embodiment can be determined by the fluorescent X-ray testing method specified in JIS H 8501 (1999).
[0048] In this embodiment, when the arithmetic mean roughness of the surface of the Ni plating layer is defined as Ra, the average distance between peaks formed on the surface of the Ni plating layer and identified by line roughness analysis is defined as D, and the average radius of curvature of the peaks formed on the surface of the Ni plating layer and identified by surface roughness analysis is defined as r, Ra×D is 0.060 to 0.400 μm. 2 and r is 0.010 to 0.500 μm. Below, Ra×D and r will be explained separately.
[0049] [About Ra×D] The arithmetic mean roughness Ra of the surface of the Ni plating layer is an index showing the size of the uneven shape of the surface of the Ni plating layer. The larger the Ra, the larger the average unevenness of the surface of the Ni plating layer. Therefore, it is considered that the larger the Ra, the larger the contact surface area between the steel foil for the current collector and the electrode mixture layer tends to be. If the contact surface area between the steel foil for the current collector and the electrode mixture layer is increased, the contact resistance occurring at the interface between the steel foil for the current collector and the electrode mixture layer can be reduced. As a result, the electrical conductivity of an electrode having the steel foil for the current collector and the electrode mixture layer is increased.
[0050] Therefore, in this embodiment, the larger Ra is preferable. In this embodiment, as long as Ra×D satisfies the range described below, Ra is not particularly limited, but is, for example, 0.02 μm or more. The preferred lower limit of Ra is 0.03 μm, and more preferably 0.04 μm. The preferred upper limit of Ra is not particularly limited. However, in the steel foil for current collector according to this embodiment, the preferred upper limit of Ra on the Ni plating layer surface is 0.50 μm from the viewpoint of production cost and productivity.
[0051] The average distance D between the peaks formed on the surface of the Ni plating layer is an index showing the density of the unevenness in the uneven shape of the surface of the Ni plating layer. The larger D is, the lower the density of the unevenness of the surface of the Ni plating layer. Therefore, it is considered that the smaller D is, the larger the contact surface area between the steel foil for the current collector and the electrode mixture layer tends to be. If the contact surface area between the steel foil for the current collector and the electrode mixture layer is increased, the contact resistance occurring at the interface between the steel foil for the current collector and the electrode mixture layer can be reduced. As a result, the electrical conductivity of an electrode having the steel foil for the current collector and the electrode mixture layer is increased.
[0052] Therefore, in this embodiment, it is preferable that D is small. In this embodiment, as long as Ra×D satisfies the range described below, D is not particularly limited, but is, for example, 2.50 μm or less. A preferred upper limit of D is 2.30 μm, and more preferably 2.00 μm. A preferred lower limit of D is not particularly limited. However, in the steel foil for current collector according to this embodiment, the lower limit of D on the surface of the Ni plating layer is, for example, 0.50 μm.
[0053] In this embodiment, further, on the surface of the Ni plating layer, Ra×D is set to 0.060 to 0.400 μm. 2 If Ra×D is too small, as described above, the electrode mixture layer may not easily penetrate into the unevenness formed on the surface of the Ni plating layer. Therefore, a gap may be generated between the Ni plating layer and the electrode mixture layer, and the surface area of contact between the steel foil for a current collector and the electrode mixture layer may become smaller. As a result, even if the arithmetic mean roughness Ra of the surface of the Ni plating layer is large, the electrical conductivity of the steel foil for a current collector on which the electrode mixture layer is formed decreases.
[0054] On the other hand, if Ra×D is too large, as described above, the number of irregularities on the surface of the Ni plating layer is small, and the surface area of contact between the Ni plating layer and the electrode mixture layer may not be sufficiently large. As a result, even if the arithmetic mean roughness Ra of the surface of the Ni plating layer is large, the electrical conductivity of the steel foil for a current collector on which the electrode mixture layer is formed decreases.
[0055] Therefore, in this embodiment, on the surface of the Ni plating layer, Ra×D is set to 0.060 to 0.400 μm.2 The preferred upper limit of Ra×D is 0.380 μm. 2 and more preferably 0.360 μm 2 and more preferably 0.330 μm 2 and more preferably 0.300 μm 2 The preferred lower limit of Ra×D is 0.070 μm. 2 and more preferably 0.080 μm 2 It is.
[0056] [About r] The average radius of curvature r of the peaks formed on the surface of the Ni plating layer is an index showing the sharpness of the uneven shape of the surface of the Ni plating layer. The smaller r is, the sharper the unevenness is. Therefore, the smaller r is, the higher the adhesion of the steel foil for a collector to the electrode mixture layer is. Therefore, in this embodiment, r is set to 0.500 μm or less. On the other hand, if r is too small, the convex parts on the surface of the Ni plating layer may be broken when the steel foil for a collector is manufactured. In this case, the broken convex parts may be mixed into the electrode mixture layer when the electrode is manufactured, and the desired performance as a battery may not be sufficiently obtained. Therefore, in this embodiment, r is set to 0.010 to 0.500 μm. The preferable lower limit of r is 0.012 μm, and more preferably 0.015 μm. The preferable upper limit of r is 0.450 μm, and more preferably 0.400 μm.
[0057] As described above, in the steel foil for a current collector according to the present embodiment, on the surface of the Ni plating layer, Ra×D is 0.060 to 0.400 μm. 2 and r is set to 0.010 to 0.500 μm. In this manner, in the present embodiment, by defining the surface roughness of the Ni plating layer without depending only on the arithmetic mean roughness Ra, it is possible to achieve both the adhesion of the current collector steel foil to the electrode mixture layer and the electrical conductivity of the electrode having the current collector steel foil and the electrode mixture layer.
[0058] [For Ra, D, and r] As described above, in this embodiment, on the surface of the Ni plating layer, the arithmetic mean roughness of the surface of the Ni plating layer is defined as Ra, the average distance between peaks formed on the surface of the Ni plating layer and identified by line roughness analysis is defined as D, and the average radius of curvature of peaks formed on the surface of the Ni plating layer and identified by area roughness analysis is defined as r.
[0059] In this embodiment, Ra, D, and r can be specified by the following method. First, a line roughness analysis is performed on the surface of the steel foil for current collector according to this embodiment to obtain a roughness curve. The cross-sectional curve for obtaining the roughness curve is obtained using a method conforming to JIS B 0601 (2013). Specifically, a line roughness measurement is performed on the surface of the steel foil for current collector according to this embodiment using a shape measuring laser microscope. The shape measuring laser microscope is not particularly limited, but for example, a shape measuring laser microscope VK-X100 manufactured by Keyence Corporation can be used. In the line roughness measurement, the magnification is 2000 times. The evaluation length is not particularly limited, but for example, 100 to 150 μm. From the result of the line roughness measurement, a cross-sectional curve is obtained in accordance with JIS B 0601 (2013). A filter with a reference length of 8 μm is applied to the obtained cross-sectional curve to obtain a roughness curve.
[0060] Preferably, the direction in which the line roughness is measured is parallel to the rolling direction of the substrate. The rolling direction of the substrate is identified by observing the surface of the steel foil for a current collector with a microscope. However, in cases where the Ni plating layer is formed thick, even a person skilled in the art may not be able to identify the rolling direction of the substrate by observing the surface of the steel foil for a current collector with a microscope. In this case, the direction in which the line roughness is measured does not have to be the rolling direction.
[0061] For the obtained roughness curve, the average of the displacements from the mean line is calculated, and this is defined as the arithmetic mean roughness Ra (μm) of the Ni plating layer surface. For the obtained roughness curve, the part above the mean line (from the steel foil for the current collector toward the space side) is further defined as a "peak" in accordance with JIS B 0601 (2013). The point with the maximum height on one peak is defined as the "peak". The number of identified peaks is counted. The evaluation length is divided by the number of peaks to obtain the average distance D (μm) between the peaks formed on the Ni plating layer.
[0062] Next, a surface roughness analysis is performed on the surface of the steel foil for current collector according to this embodiment to obtain a measured surface. Specifically, a surface roughness measurement is performed on the surface of the steel foil for current collector according to this embodiment using a shape measuring laser microscope. The shape measuring laser microscope is not particularly limited, but for example, a shape measuring laser microscope manufactured by Keyence Corporation (product name: Shape Measuring Laser Microscope VK-X100) can be used. The magnification for the surface roughness measurement is 2000 times. The evaluation area is not particularly limited, but for example, a 10000 μm 2 From the results of the surface roughness measurement, the measurement surface is obtained using a method conforming to ISO 25178:2012. The reference length is 25 μm.
[0063] For the obtained measurement surface, the portion above the reference surface (in the direction from the steel foil for the current collector toward the space side) is defined as the "mountain". For one mountain, the point with the maximum height is defined as the "peak". The radius of curvature is calculated for the identified peak. The arithmetic mean value of the obtained radii of curvature is calculated, and this is defined as the average radius of curvature r (μm) of the peaks formed on the Ni plating layer surface.
[0064] That is, in this embodiment, the arithmetic mean roughness Ra of the Ni plating layer surface is defined as the average of the displacements from the mean line in the roughness curve obtained by measuring at a magnification of 2000 times in accordance with JIS B 0601 (2013) and applying a filter with a reference length of 8 μm. In this embodiment, the average distance D between the peaks formed on the Ni plating layer surface and identified by line roughness analysis is defined as the average distance between the peaks when the parts above the mean line are defined as "peaks" and the points with the maximum heights of the peaks are defined as "peaks" in the roughness curve obtained by measuring at a magnification of 2000 times in accordance with JIS B 0601 (2013) and applying a filter with a reference length of 8 μm. In this embodiment, the average radius of curvature r of the peaks formed on the surface of the Ni plating layer and identified by surface roughness analysis is defined as the arithmetic average value of the radii of curvature of the peaks, in a measurement surface obtained in accordance with ISO 25178:2012, measured at a magnification of 2000 times, and with a reference length of 25 μm, where the parts above the reference surface are defined as "peaks" and the points at which each peak has the maximum height are defined as "peaks."
[0065] The steel foil for a current collector according to the present embodiment may further have a plating layer on the surface of the substrate. Preferably, the surface of the substrate has a Ni plating layer. In this case, the formation of an oxide film on the surface of the substrate is suppressed, and the electrical conductivity of the steel foil for a current collector is further improved. In this case, the adhesion between the substrate and the Ni plating layer is further improved. When a Ni plating layer is formed on the surface of the substrate, the Ni plating layer formed on the surface of the substrate and the Ni plating layer having an uneven surface, which will be described later, are integrated.
[0066] [electrode] The electrode according to the present embodiment includes the above-mentioned steel foil for a current collector and an electrode mixture layer formed on the surface of the steel foil for a current collector. The electrode according to the present embodiment may be a positive electrode or a negative electrode. That is, the electrode is not particularly limited as long as it includes the above-mentioned steel foil for a current collector and an electrode mixture layer.
[0067] [Electrode mixture layer] In this embodiment, the electrode mixture layer is not particularly limited, and may have a well-known configuration. The electrode mixture layer includes an active material and a binder. The electrode mixture layer may contain a composition other than the active material and the binder. The electrode mixture layer may contain, for example, a conductive assistant. The conductive assistant helps improve the electrical conductivity of electrons.
[0068] [Active material] In this embodiment, the active material is not particularly limited, and a well-known active material can be used. The active material is a powder particle that does not dissolve in the electrolyte described later. When the electrode is a negative electrode, the negative electrode active material may be, for example, a carbon-based material represented by graphite, an alloy material represented by a CuSn alloy or a NiTiSi alloy, or a Si-based material represented by SiO. When the electrode is a positive electrode, the positive electrode active material may be, for example, lithium cobalt oxide, a ternary material, lithium manganate, lithium iron phosphate, or high nickel. In other words, both the positive electrode active material and the negative electrode active material may be of a well-known configuration and are not particularly limited.
[0069] [Binding agent] In this embodiment, the binder is not particularly limited, and a well-known binder can be used. For example, the binder may be a water-insoluble resin that is insoluble in a solvent used in the non-aqueous electrolyte of the battery, a water-soluble resin, or styrene butadiene rubber (SBR). Examples of the water-insoluble resin that is insoluble in a solvent used in the non-aqueous electrolyte of the battery include polyimide (PI), polyvinylidene fluoride (PVDF), polymethyl methacrylate (PMMA), and polytetrafluoroethylene (PTFE). Examples of the water-soluble resin include carboxymethyl cellulose (CMC) and polyvinyl alcohol (PVA).
[0070] The electrode according to the present embodiment includes the above-mentioned steel foil for a current collector and a well-known electrode mixture layer formed on the surface of the steel foil for a current collector. As a result, the electrode according to the present embodiment has high adhesion between the steel foil for a current collector and the electrode mixture layer, and has high electrical conductivity.
[0071] [battery] The battery according to the present embodiment includes the above-mentioned electrodes, a separator, and an electrolyte. The battery according to the present embodiment may have other known configurations as long as it includes the electrodes including the above-mentioned steel foil for current collector, and is not particularly limited. The shape of the battery according to the present embodiment is not particularly limited, and may be cylindrical, rectangular, coin-shaped, or sheet-shaped. The battery according to the present embodiment may be a secondary battery or a primary battery. When the battery according to the present embodiment is a secondary battery, it may be, for example, a non-aqueous electrolyte secondary battery, an aqueous electrolyte secondary battery, or an all-solid-state secondary battery.
[0072] [Separator] The separator is disposed between the positive electrode and the negative electrode as an insulator, and prevents electrical short circuit from occurring. In this embodiment, the separator is not particularly limited, and a well-known separator can be used. The separator may be, for example, a polyolefin-based material such as polypropylene or polyethylene, or a mixture of both, or may be a porous body such as a glass filter.
[0073] [Electrolyte] The electrolyte exchanges ions with the positive electrode and the negative electrode. In the present embodiment, the electrolyte is not particularly limited, and a well-known electrolyte can be used. The electrolyte may be a liquid electrolyte solution or a solid electrolyte.
[0074] The battery according to the present embodiment includes the above-mentioned electrode, a known separator, and a known electrolyte. As a result, the electrode according to the present embodiment has high adhesion between the current collector steel foil and the electrode mixture layer, and has high electrical conductivity.
[0075] [Adhesion] The steel foil for a current collector according to this embodiment has high adhesion to an electrode mixture layer. In this embodiment, the adhesion of the steel foil for a current collector to an electrode mixture layer can be evaluated by the following method.
[0076] A test piece is prepared from the steel foil for current collector according to the present embodiment. Specifically, the composition for the electrode mixture layer is applied to the steel foil for current collector and dried. The size of the steel foil for current collector is not particularly limited, but for example, 210 mm in length and 148 mm in width. The composition for the electrode mixture layer is not particularly limited, but for example, NiTiSi alloy powder, styrene butadiene rubber (SBR), and carboxymethyl cellulose (CMC) are mixed in a ratio of 95:4:1 and kneaded. In this case, water is used as a solvent. The composition for the electrode mixture layer is applied to the test piece with an applicator having a coating width of 80 mm and a gap of 200 μm. At this time, the composition is applied so that the uncoated parts are 34 mm on each side. The applied composition is heated at 75° C. for 20 minutes and dried. A test piece is cut out from the electrode after drying. The size of the test piece is not particularly limited, but for example, it is 15 mm in width and 74 mm in length (coated part 40 mm). In the above manner, a test piece having an electrode mixture layer formed thereon is prepared.
[0077] A double-sided tape is applied to the electrode mixture layer of the test piece, and the test piece is attached to a stainless steel plate. The region of the test piece where the electrode mixture layer is not formed is vertically lifted to peel off the electrode mixture layer. The test piece is lifted at a speed of 50 mm / min. At this time, a force gauge is attached to the test piece to measure the peel strength (N / m). In this embodiment, if the peel strength is 25.0 N / m or more, the steel foil for a current collector can be evaluated as having high adhesion to the electrode mixture layer.
[0078] [Electrical Conductivity] The steel foil for a current collector according to this embodiment has high electrical conductivity when an electrode mixture layer is formed on the surface. In this embodiment, the electrical conductivity of the steel foil for a current collector having an electrode mixture layer formed thereon can be evaluated by the following method.
[0079] An electrode mixture layer is formed on the current collector steel foil according to this embodiment in the same manner as in the above-mentioned test for evaluating adhesion. A test piece is prepared from the current collector steel foil on which the electrode mixture layer is formed. Furthermore, an electrode mixture layer is also formed on a stainless steel foil not having a Ni plating layer in the same manner as in the above-mentioned test for evaluating adhesion, to prepare a control test piece. The test piece and the control test piece have the same thickness. The size of the test piece and the control test piece is not particularly limited, but may be, for example, a circular shape with a diameter of 15 mm.
[0080] The penetration resistance of the test piece is measured using a resistance meter. The resistance meter is not particularly limited, but for example, a resistance meter RM3544 (trade name) manufactured by Hioki E.E. Corporation can be used. Specifically, the test piece is clamped between Cu terminals, and a resistance of 0.6 kgf / cm 2 A load of 0.70 is applied. The test piece is surrounded by an insulator, and the resistance value (Ω) of the test piece is determined using the resistance meter. A similar test is also performed on the control test piece. The ratio of the resistance value (Ω) of the test piece to the resistance value (Ω) of the control test piece is defined as the penetration resistance (relative value). In this embodiment, if the penetration resistance (relative value) is 0.70 or less, the steel foil for a current collector on which an electrode mixture layer is formed can be evaluated as having high electrical conductivity.
[0081] [Manufacturing method of steel foil for current collectors] An example of a method for manufacturing a steel foil for a current collector according to the present embodiment will be described. The manufacturing method described below is one example for manufacturing a steel foil for a current collector according to the present embodiment, and the manufacturing method of the steel foil for a current collector according to the present embodiment may be a manufacturing method other than the manufacturing method described below. However, the manufacturing method described below is a preferred example of the manufacturing method of a steel foil for a current collector according to the present embodiment. The manufacturing method of a steel foil for a current collector according to the present embodiment includes a base material preparation step and a Ni plating layer formation step.
[0082] [Base material preparation process] In the substrate preparation step, a substrate for a steel foil for a current collector is prepared. The method for preparing the substrate is not particularly limited and may be a well-known method. For example, the method for preparing the substrate may be to prepare an intermediate steel material having a desired chemical composition and cold work the intermediate steel material to prepare the substrate. This case will be specifically described below.
[0083] The intermediate steel material having a desired chemical composition can be appropriately set according to the mechanical properties of the substrate to be obtained. Here, the intermediate steel material means a steel sheet having a thickness of several hundred μm to several mm. The intermediate steel material may be a stainless steel sheet or a plated steel sheet.
[0084] When preparing a substrate by cold working an intermediate steel material, a preferred cold working is cold rolling. Cold rolling can be performed using a known device. For example, a multiple reversing cold rolling mill may be used. In this case, the degree of working in the cold rolling is not particularly limited. The degree of working can be set appropriately depending on the thickness of the substrate to be obtained. In addition, the substrate after cold rolling may be appropriately heat-treated.
[0085] As described above, in the preparation step, a substrate is prepared. The substrate may be manufactured by the above-mentioned preferred steps, or a substrate manufactured by a third party, or a substrate manufactured in a factory or business establishment other than the factory where the Ni plating layer forming step described later is performed may be prepared. In short, the preparation step in this embodiment is not particularly limited, and may be a well-known method.
[0086] As described above, the substrate may have a plating layer on its surface. When forming a plating layer on the substrate, preferably, the plating layer is formed on the surface of an intermediate steel material, and then cold rolling is performed. In this case, the plating layer on the substrate surface can be formed thin. Preferably, a Ni plating layer is formed on the surface of the intermediate steel material. In this case, for example, an intermediate steel material (having a thickness of several hundred μm) having a Ni plating layer is cold rolled to obtain a substrate having a thickness of 50 μm or less. The method for forming the Ni plating layer is not particularly limited, and may be a well-known method.
[0087] [Ni plating layer formation process] In the Ni plating layer forming step, a Ni plating layer is formed on the surface of a prepared base material. Specifically, the surface of the prepared base material is washed with alcohol. The alcohol is, for example, isopropanol. The plating solution for forming the Ni plating layer contains Ni(NH2SO3)2 and CaCl2. The concentration of Ni(NH2SO3)2 in the plating solution is 1.0 to 2.0 mol / L, and the concentration of CaCl2 is 0.5 to 3.0 mol / L. The base material with the washed surface is immersed in the plating solution held at 40 to 80°C, and a current of 2 to 10 A / dm is applied. 2 A current of 10 to 120 seconds is applied. At this time, the cathode is the substrate and the anode is a Ni steel plate. The time for which the current is applied is, for example, 10 to 120 seconds.
[0088] Preferably, a base plating layer is formed before the above-mentioned Ni plating layer forming step. The chemical composition of the base plating layer is preferably composed of Ni and impurities. That is, preferably, a base Ni plating layer is formed before the above-mentioned Ni plating layer forming step. In this case, the adhesion between the substrate and the Ni plating layer is improved.
[0089] [Plating layer formation process] The undercoat plating layer forming step is carried out optionally. That is, the undercoat plating layer forming step does not have to be carried out. When carried out, it is carried out after the preparation step and before the Ni plating layer forming step. Specifically, the surface of the prepared base material is washed with alcohol. The alcohol is, for example, isopropanol. The plating solution for forming the undercoat plating layer contains NiSO4 and NiCl2. The concentration of NiSO4 in the plating solution is 1.3 to 1.9 mol / L, and the concentration of NiCl2 is 0.3 to 0.6 mol / L. The base material with the washed surface is immersed in the plating solution held at 40 to 80°C, and is plated with 2 to 10 A / dm 2 A current of 10 to 120 seconds is applied. At this time, the cathode is the substrate and the anode is a Ni steel plate. The time for which the current is applied is, for example, 10 to 120 seconds.
[0090] The steel foil for a current collector according to the present embodiment can be manufactured by the above steps. As described above, the manufacturing steps described above are a preferred example for manufacturing the steel foil for a current collector according to the present embodiment, and the manufacturing method of the steel foil for a current collector according to the present embodiment is not limited to the above method.
[0091] [Electrode manufacturing method] An example of a method for manufacturing an electrode using the steel foil for a current collector according to the present embodiment is as follows: The method for manufacturing an electrode according to the present embodiment includes an electrode mixture preparing step and an electrode mixture layer forming step.
[0092] [Electrode mixture preparation process] In the electrode mixture preparation step, a composition for forming an electrode mixture layer is prepared. The composition for forming the electrode mixture may be prepared according to the electrode mixture layer to be obtained. For example, the composition is prepared by kneading an active material and a binder. For example, the composition may be prepared by kneading an active material, a binder, and a conductive assistant. For example, the composition may be prepared by kneading an active material, a binder, and a solvent. The kneading method is appropriately adjusted according to the active material, the binder, the conductive assistant, and the solvent. That is, the electrode mixture preparation step may be performed by a well-known method.
[0093] [Electrode mixture layer formation process] In the electrode mixture layer forming step, an electrode mixture layer is formed on the surface of the above-mentioned steel foil for a current collector. Specifically, a composition for forming the kneaded electrode mixture is applied to the above-mentioned steel foil for a current collector. The method of application is not particularly limited and may be a well-known method. For example, the composition may be applied to the steel foil for a current collector using an applicator with a gap. For example, the composition may be further sprayed onto the steel foil for a current collector using a sprayer.
[0094] The composition applied on the steel foil for the current collector is then dried to form an electrode mixture layer. The drying method is not particularly limited and may be a well-known method. For example, the composition may be dried by heating at 75°C for 20 minutes. For example, the composition may be dried without further heating.
[0095] The electrode according to the present embodiment can be manufactured by the above steps. As described above, the manufacturing steps described above are a preferred example for manufacturing the electrode according to the present embodiment, and the manufacturing method of the electrode according to the present embodiment is not limited to the above method.
[0096] [Battery manufacturing method] The method for manufacturing the battery according to the present embodiment is not particularly limited. The battery according to the present embodiment is manufactured by laminating the above-mentioned electrode, separator, and counter electrode by a known method. The laminate is placed in a case to manufacture the battery. EXAMPLES
[0097] The substrates of each test number shown in Table 1 were prepared. The size of the substrate of each test number was a rectangle of 297 mm in length and 210 mm in width, with the longitudinal direction parallel to the rolling direction. The "Ni-plated steel foil" in the "Substrate" column of Table 1 means a Ni-plated steel foil having a thickness of 10 μm. The Ni-plated steel foil was prepared by cold rolling a Ni-plated steel sheet having a thickness of 100 μm. The base material of the Ni-plated steel foil was ultra-low carbon steel. The "Stainless steel foil A" in the "Substrate" column of Table 1 means a ferritic stainless steel foil having a thickness of 10 μm and corresponding to SUS430 as specified in JIS G 4305 (2012). The "Stainless steel foil B" in the "Substrate" column of Table 1 means a ferritic stainless steel foil having a thickness of 10 μm and corresponding to SUS444 as specified in JIS G 4305 (2012).
[0098] [Table 1]
[0099] A base plating layer was formed on the substrates with some of the test numbers. Specifically, a base plating layer was formed on the substrates with test numbers that are marked as "Implemented" in the "Base plating layer formation" column in Table 1. Specifically, the surface of the substrate with the corresponding test number was washed with isopropanol for 30 seconds and then washed with pure water for 30 seconds. The washed substrate was immersed in a plating solution to form a base plating layer (Ni plating layer) with a thickness of 1 μm. The plating solution contained 1.9 mol / L NiSO4 and 0.4 mol / L NiCl2. The temperature of the plating solution was 50°C, and the current value was 5 A / dm 2 The current application time was 70 seconds. For the test numbers with "-" in the "Base plating layer formation" column in Table 1, a base plating layer was not formed on the substrate.
[0100] Furthermore, a Ni plating layer was formed on the substrates with some of the test numbers. Specifically, a Ni plating layer was formed on the substrates with test numbers that are marked as "Implemented" in the "Ni plating layer formation" column in Table 1. Specifically, the surface (undercoat plating layer surface) of the substrate with the corresponding test number was washed with isopropanol for 30 seconds and then washed with pure water for 30 seconds. The washed substrate was immersed in a plating solution to form a Ni plating layer. The plating solution contained Ni(NH2SO3)2 at 1.5 mol / L and CaCl2 at the concentrations listed in Table 1. The plating solution was at 60°C and the current value was 5 A / dm 2 The current flow time was as shown in Table 1. For the test numbers with "-" in the "Ni plating layer formation" column in Table 1, a Ni plating layer was not formed on the substrate.
[0101] For the steel foils for current collectors having the respective test numbers produced as described above, a Ni plating layer thickness measurement test, a surface roughness measurement test, an electrical conductivity evaluation test, and an adhesion evaluation test were carried out.
[0102] [Ni plating layer thickness measurement test] The thickness of the Ni plating layer was measured for the steel foil for current collector of each test number. The thickness of the Ni plating layer was measured by a fluorescent X-ray test in accordance with JIS H 8501 (1999). The thickness of the Ni plating layer obtained for each test number is shown in Table 2.
[0103] [Table 2]
[0104] [Surface roughness measurement test] For the steel foil for current collector of each test number, the arithmetic mean roughness Ra (μm) of the surface of the Ni plating layer, the average distance D (μm) between the peaks formed on the surface of the Ni plating layer, and the average radius of curvature r (μm) of the peaks formed on the surface of the Ni plating layer were obtained by the above-mentioned method. The line roughness measurement and the surface roughness measurement were performed using a shape measuring laser microscope VK-X100 manufactured by Keyence Corporation. The line roughness measurement was performed at three arbitrary locations in the longitudinal direction (rolling direction) of the steel foil for current collector. From the line roughness measurement, the arithmetic mean roughness Ra and the average distance D between the peaks obtained by the above-mentioned method were obtained, and the arithmetic mean value was used. The surface roughness measurement was performed by the above-mentioned method, and the average radius of curvature r of the peaks obtained was obtained. The obtained Ra (μm), D (μm), r (μm) of each test number, and the Ra×D (μm) obtained from these were used. 2 ) are shown in Table 2.
[0105] [Electrical conductivity evaluation test] The electrical conductivity of the collector steel foil of each test number was evaluated by the method described above. Three test pieces were prepared for each test number, and the penetration resistance was determined three times for each test piece. The arithmetic mean value of the nine obtained penetration resistances (relative values) was taken as the penetration resistance (relative value) for each test number. The obtained penetration resistance (relative value) for each test number is shown in Table 2.
[0106] [Adhesion evaluation test] The adhesion of the steel foil for current collector of each test number to the electrode mixture layer was evaluated using the method described above. Four test pieces were prepared for each test number, and the peel strength (N / m) was determined for each. The arithmetic mean value of the four obtained peel strengths was taken as the peel strength (N / m) for each test number. The obtained peel strength (N / m) for each test number is shown in Table 2.
[0107] [Evaluation Results] Referring to Tables 1 and 2, the steel foils for current collectors of Test Nos. 1 to 12 have a Ni plating layer formed on the surface of the substrate, and have Ra×D of 0.060 to 0.400 μm. 2 and r was 0.010 to 0.500 μm. As a result, the penetration resistance (relative value) was 0.70 or less, indicating high electrical conductivity. As a result, the peel strength was 25.0 N / m or more, indicating high adhesion.
[0108] On the other hand, the steel foil for the collector of test number 13 has an Ra×D of 0.060 μm. 2 As a result, the penetration resistance (relative value) exceeded 0.70, and high electrical conductivity was not observed.
[0109] The current collector steel foils of test numbers 14 and 15 had r exceeding 0.500 μm, and as a result, the peel strength was less than 25.0 N / m, and did not exhibit high adhesion.
[0110] The steel foils for the collectors of test numbers 16 and 17 had an Ra×D of 0.060 μm. 2 The surface roughness was less than 0.500 μm, and r exceeded 0.500 μm. As a result, the penetration resistance (relative value) exceeded 0.70, and high electrical conductivity was not exhibited. As a result, the peel strength was less than 25.0 N / m, and high adhesion was not exhibited.
[0111] In the steel foils for current collectors of test numbers 18 and 19, no Ni plating layer was formed on the surface of the substrate. Furthermore, r exceeded 0.500 μm. As a result, the penetration resistance (relative value) exceeded 0.70, and high electrical conductivity was not exhibited. As a result, the peel strength was less than 25.0 N / m, and high adhesion was not exhibited.
[0112] The embodiments of the present disclosure have been described above. However, the above-described embodiments are merely examples for implementing the present disclosure. Therefore, the present disclosure is not limited to the above-described embodiments, and can be implemented by appropriately modifying the above-described embodiments without departing from the spirit of the present disclosure.
Claims
1. A steel foil for a current collector, A substrate and a Ni plating layer formed on a surface of the substrate, When the arithmetic mean roughness of the surface of the Ni plating layer is defined as Ra, the average distance between peaks formed on the surface of the Ni plating layer and identified by line roughness analysis is defined as D, and the average radius of curvature of the peaks formed on the surface of the Ni plating layer and identified by area roughness analysis is defined as r, Ra×D is 0.060 to 0.400 μm 2 and r is 0.010 to 0.500 μm; Steel foil for current collectors.
2. The steel foil for a current collector according to claim 1, The average thickness of the substrate is 5 to 30 μm. Steel foil for current collectors.
3. The steel foil for a current collector according to claim 1 or 2, An electrode mixture layer formed on the surface of the current collector steel foil, electrode.
4. An electrode according to claim 3; A separator; an electrolyte; battery.
Citation Information
Patent Citations
Negative electrode for lithium secondary battery and its manufacturing method
JP2008098094A
Lithium ion secondary battery negative electrode and lithium ion secondary battery
JP2011258407A
Copper-coated steel foil, negative electrode collector and method for manufacturing the same, and battery
JP2012033470A
Negative electrode and method for manufacturing of the same
KR1020170044322A
Negative electrode collector for nonaqueous electrolyte secondary battery
WO2005057693A1